Racial Disparities in Inpatient Hospital Outcomes of Primary Sclerosing Cholangitis in United States: Nationwide Analysis - Ishaan Vohra; Harishankar Gopakumar; Dushyant Singh Dahiya; Michel Kahaleh; Neil Sharma (Diagnostics)
Background: Primary sclerosing cholangitis (PSC) is an idiopathic cholestatic liver disease that may lead to biliary strictures and destruction. It is associated with p-ANCA positivity and inflammatory bowel disease, typically ulcerative colitis. The aim of this study is to investigate the trends of inpatient healthcare utilization and mortality from 2008 to 2017 in the United States. Methods: The Nationwide Inpatient Sample (NIS) was examined to identify adult patients diagnosed with PSC between 2008 and 2017. Data on patient demographics, resource utilization, mortality, and PSC-related complications were collected. STATA version 16.0 was employed to perform forward stepwise multivariate regression analysis, generating adjusted odds ratios for both primary and secondary outcomes. Primary outcomes included the inpatient mortality rate and healthcare resource utilization (length of stay, total charges, and trends over the study period). Secondary outcomes focused on trends in associated comorbidities and malignancies in patients with PSC. Results: The average total charge increased by 32.2% ± 2.12 from USD 61,873 ± 2567 in 2008 to USD 91,262 ± 2961 in 2017. Concurrently, the average length of stay declined from 8.07 ± 0.18 days in 2008 to 7.27 ± 0.13 days in 2017. The APR-DRG severity of illness and risk of death significantly increased (major or extreme) during the study period (2008 to 2017), with severity rising from 73.6% to 82.7% (coefficient: 0.21, 95% CI: 0.13–0.28) and risk of death from 45.3% to 60.9% (coefficient: 0.15, 95% CI: 0.08–0.23). The proportion of patients with HCC increased from 1.3% to 7.9% (coefficient: 2.13, 95% CI: 1.9–2.8). Conversely, the percentage of patients with cholangiocarcinoma (CCA) decreased from 5.1% to 2.8% (coefficient: −0.36, 95% CI: −0.25 to −0.46). Conclusions: There was rising mortality and healthcare resource utilization among patients with PSC from the years 2008 to 2017. These trends were paralleled by increasing rates of decompensated cirrhosis, HCC, and liver transplants. However, the incidence of CCA decreased during this time period. African American patients with PSC had worse inpatient mortality outcomes and healthcare utilization as compared to white patients. Further studies are warranted to investigate a possible causal link amongst these trends.